Term Hidayah Dalam Al-Qur’an : Kajian Terhadap Penafsiran Al-Zamakhshari Dan Wahbah Zuhaili - Muhamad Fathul Arifin; Muhajirin (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2024)
Every word in the Qur'an has a unique meaning that needs to be understood, including the word hidayah which means guidance. In reality, not everyone can get the guidance, there are even servants whose lives are completely fulfilled, but are not given guidance. On the other hand, there are servants who do not have a strong Islamic knowledge base, but Allah gives them guidance to get closer to Him. Therefore, this article examines the meaning of guidance according to the views of al-Zamakhshari as a mufassir bi al-ra'yi and Wahbah Zuhaili with a combination of bi al-ra'yi and bi al-ma'tsuur interpretations. The analysis of the meaning of Hidayah aims to find out its essence and the way to obtain it. The term Hidayah is analyzed using the Muqarran tafsir method which is used to compare the views of the two mufassirs about the term Hidayah. From the results of the analysis and review, it is found that guidance is essentially purely from Allah SWT, which will be given to His servants who are willing and open their hearts to receive guidance themselves. Keywords: Hidayah, al-Zamakhshari, Wahbah Zuhaili, Tafsir Muqarran.